Memory and conceptual learning of relevant and non-relevant items in item-method directed forgetting. Issue 9 (21st October 2018) - Orghian, Diana; Garcia-Marques, Leonel; Marques, Pedro; Braga, João
ABSTRACT: The present research investigates the fate of non-target information when people are trying to either intentionally memorise or forget target information. By using an object-based attentional manipulation within a directed forgetting paradigm (item-method), we show a directed forgetting effect (DFE, i.e., better memory for to-be-remembered (TBR) than for to-be-forgotten (TBF) items) for items that participants are explicitly instructed to attend but not for irrelevant items that happen to be part of the context. Alongside the classic DFE, we investigate how the category of the attended and unattended items are learned. The results obtained in three experiments, show that people can successfully learn only the category of the TBR attended items and that the DFE extends to new items that are related to the old TBR and TBF items (an effect that we call conceptual DFE). These results give us new insight about how TBR and TBF items are processed and conceptually learned.